A Comparative Evaluation of Corneal Endothelium between Diabetic & Non-Diabetic Patients Undergoing Phacoemulsification in a Tertiary Hospital (Journal of National Institute of Ophthalmology, 2022)
Objective: To compare changes of corneal endothelium after phacoemulsification in diabetic patient comparison to non-diabetic patient.Methods: This prospective observational study was conducted over 100 patients in a tertiary hospital from 01st January to 30th July 2020. Patients were selected purposively based on specific selection criteria. Patients were allocated into two groups: Group-I: cataract patient without diabetes mellitus and Group-II: cataract patient with diabetes mellitus. Selected patients underwent detailed ophthalmic and systemic examination as well as relevant laboratory investigation. Phacoemulsification was done in every patient by a single experienced surgeon under local anesthesia. Patients were evaluated pre-operatively, 7th POD and after one month post-operatively. In each visit, visual acuity, endothelial cell count, endothelial hexagonality, cell variability and central corneal thickness were recorded. All the relevant data were recorded in a pre-designed data collection sheet.Results: The mean age of patients in group I and II were 54.40+3.22(SD) and 54.86+3.07(SD) years respectively. In group I, 29 (58%) were male and 21(42%) were female whereas in group II, 33 (66%) were male and 17(34%) were female. In Group-I, visual acuity in preoperative period, 7th POD and after one month were 0.734, 0.232 and 0.148 respectively and in Group-II, preoperatively, 7th POD and after one month were - 0.730, 0.260 and 0.148 respectively. In group I, Endothelial cell count per square millimeter in preoperative, 7th POD and after one month were- 2681.76, 2543.62 and 2518.68 respectively and in Group-II, preoperative, 7th POD and after one month were - 2596.62, 2378.84 and 2270.46 respectively. Hexagonality of endothelial cell count in group-I, pre-operative, 7th POD and after one month value were 64.34, 61.08 and 59.12; in group-II, pre-operative, 7th POD and after one month value were 63.80, 56.04 and 53.10 respectively. Cell size variability in group-I, pre-operative, 7th POD and after one month value were 30.76, 33.96 and 35.42; in group-II, pre-operative, 7th POD and after one month value were 29.58, 33.90 and 35.98 respectively. Central corneal thickness in group-I, pre-operative, 7th POD and after one month value were 534.04, 589.12 and 560.68; in group-II, pre-operative, 7th POD and after one month value were 530.12, 630.24 and 569.94 respectively.Conclusion: By analyzing the results and findings, it may be concluded that corneal endothelium was greatly changed after phacoemulsification in diabetic patient in compare to non-diabetic patient.J. Natl. Inst. Ophthalmol. 2022; 5(2):9-15